2014
DOI: 10.1128/jcm.02369-14
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Surveillance Testing for Multidrug-Resistant Gram-Negative Bacteria in the Intensive Care Unit

Abstract: f We tested intensive care unit patients for colonization with multidrug-resistant Gram-negative bacilli (MDR GNB) and compared the results with those of concurrent clinical cultures. The sensitivity of the surveillance test for detecting MDR GNB was 58.8% (95% confidence interval, 48.6 to 68.5%). Among 133 patients with positive surveillance tests, 61% had no prior clinical culture with MDR GNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On one side, we plan to perform metagenomic sequencing and resistome analysis to detect subclinical gut colonization. It has been documented a low sensitivity of culture-based methods aimed to surveillance of MRGNB carriers [ 19 ]. This could be more frequent at the beginning of colonization, when the proportion of multi-resistant bacteria in the microbiota is still a minority.…”
Section: Discussionmentioning
confidence: 99%
“…On one side, we plan to perform metagenomic sequencing and resistome analysis to detect subclinical gut colonization. It has been documented a low sensitivity of culture-based methods aimed to surveillance of MRGNB carriers [ 19 ]. This could be more frequent at the beginning of colonization, when the proportion of multi-resistant bacteria in the microbiota is still a minority.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance culture-based methods have demonstrated to be effective for the early detection of colonized patients by ESBL- and/or carbapenemase-producing Enterobacterales and are routinely performed in many hospitals, mainly in intensive care units and hematology wards [ 7 , 8 , 9 ]. This screening allows taking infection control measures rapidly, but also to adjust proper empirical antimicrobial regimes, once the infection develops.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both overtreatment in non-colonized patients and undertreatment in colonized patients can be avoided, situations which are generally associated with an increase of infectious mortality [ 9 ]. Despite its usefulness, some studies found that culture-based methods are not sensitive enough for the detection of all cases of colonization by MDR Gram-negative bacteria [ 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%